Determinants of Financial Reporting Timeliness and its Effect on Firm Value in Properties and Real Estate Sector Companies Listed on the Indonesia Stock Exchange - Retnowati, Wulan; Rahayu, Nur; Satibi, Muhammad (PT. EQUATOR SINAR AKADEMIA, 2025)
The research aims to examine the impact of audit committee size, audit committee expertise, audit committee meeting frequency, audit committee independence, and audit committee gender diversity on the timeliness of financial reporting and its effect on firm value. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2022. The sampling technique used is purposive sampling, resulting in a sample of 44 companies. This study employs a quantitative approach utilizing secondary data obtained from the Indonesia Stock Exchange. The model applied includes logistic regression analysis to test hypotheses 1 through 5, and simple linear regression analysis for hypothesis 6, using SPSS 25 software. The findings indicate that Audit Committee Size has a negative effect on the timeliness of financial reporting. Audit Committee Meeting Frequency and Audit Committee Gender Diversity both factors have a positive impact on the timeliness of financial reporting. Audit Committee Expertise and Audit Committee Independence these variables do not significantly affect the timeliness of financial reporting. Furthermore, the consequence variable shows that the timeliness of financial reporting negatively affects firm value.